Profile of Mathematical Creative Thinking in Students Type Sensing and Intuiting Personality in Resolving Mathematical Problems - Bangun Susilo (EduResearch Mitra Inovasi, 2019)
A good country is a country that is able to deal with any changes quickly. Preparing good human resources is the best way to deal with it. The 2013 curriculum is designed to prepare qualified generations, one of which is having the ability to think creatively. A person's thinking ability is of course different, so is his personality. This study aims to describe the profile of students' creative mathematical thinking sensing and intuitive personality types in solving mathematical problems. This research is a descriptive study with a qualitative approach. There were 4 subjects in this study, 2 students with sensing personality types and 2 student subjects with intuitive personality types. The data obtained in the study were personality test results, interview tests and problem solving tests. Problem solving tests were analyzed using TTCT based on existing components. The results show that students with intuitive personality types have a higher level of creativity than students with sensing personality types. These differences can be seen from the way students respond to problems or problems given. Students with intuitive personalities more quickly adjust to the problems given. While students with sensing personality need considerable time in terms of adjusting to the problems given.